Obesity as a Multidisciplinary Challenge - Mazur, Aleksandra; Sajewicz, Krzysztof; Dulęba, Julia; Strzałkowska , Paulina; Kin, Filip; Koszałko , Joanna; Kaźmierczak, Monika; Hobot, Maciej; Kalisiak, Julia; Geworkian, Nel (Quality in Sport, 2026)
Purpose. Obesity is a chronic metabolic disease that has reached epidemic proportions worldwide, affecting individuals across all ages, genders, and socioeconomic backgrounds. Its growing prevalence presents a significant public health issue due to the various complications it leads to, such as metabolic disorders, cardiovascular diseases, and psychological or social problems. The aim of this article is to analyze the effectiveness of current therapeutic approaches to obesity, with particular focus on dietary interventions, pharmacotherapy, psychotherapy, and surgical treatment. Materials and Methods. This article is based on a literature review of obesity treatment methods. Data from clinical trials, meta-analyses, and clinical guidelines were selected through searches in databases such as PubMed and Google Scholar. Keywords are “obesity”, “diet”, “anti-obesity drugs”, “pharmacotherapy”, “psychotherapy” and “bariatric surgery.” Priority was given to studies published between 2020 and 2025. Findings. This review provides an overview of current obesity treatment strategies. While dietary changes are the key element of treatment, combining them with pharmacotherapy and psychological support enhances effectiveness and leads to better long-term outcomes. Surgical intervention is reserved for severe cases after other methods have been explored. Each approach is assessed for its effectiveness, safety, and role within a comprehensive treatment plan.